685 Food Allergy - Gastro-Esophageal Reflux Disease Association in Infants. (October 2012) - Cazan, C; Dobrota, L; Neamtu, ML
Abstract : Background: Cow's milk allergy is considered to be the first and most common type of allergy during early infancy. Gastro-esophageal reflux disease and cow's milk allergy are two different diseases with common clinical features. The aim: of the study was to evaluate the clinical data in relation with gastroesophageal reflux and cow's milk allergy in infants. Material and Methods: The prospective study includes 36 infants aged between 2–6 months who attended at Pediatric Clinic during the year 2011 for the clinical evocative manifestations of gastroesophageal reflux. Study protocol includes: clinical criteria, familial/personal atopic features, mother diet, duration of breastfeeding, infant formula, esophageal ultrasonographic study, serum specific IgE cow's milk. Results: The clinical presentations of the infants were associated or isolated agitation/irritability, feeding refusal (p<0.0002), poor weight gain (p<0.0001), vomiting, wheezing, apnea and atopic dermatitis. Specific Ig E revealed allergy in 10 cases. The implication of cow's milk allergy was in 10/36 cases (27.7%). The key elements evocating the link between cow's milk allergy and gastroesophageal reflux were the persistence of symptoms under anti-reflux therapy and the improvement of symptoms under the exclusion of cow's milk. Favorable clinical course, disappearance of symptoms, weight gain under anti-reflux therapy confirmed the gastroesophagial reflux in the other cases. Esophageal ultrasonography was a useful noninvasive test in patients with reflux. Conclusions: Clinical assessment and allergy tests in infants with the suspicion of gastroesophageal reflux revealed the association of these diseases. The concomitant therapy was followed by clinical resolution of symptoms.